How the provision of inflation information affects pension contributions: A field experiment - Pascal Büsing; Henning Cordes; Thomas Langer (Journal of Risk and Insurance, 2023)
Ignoring the effects of inflation in retirement planning can have severe consequences for an individual's future financial well-being. Yet, many pension funds do not communicate inflation-related information, presumably for the fear of reduced contributions once the members understand how low the “real” return on saving for retirement is. As an alternative prediction, the provision of inflation information could increase pension contributions, because it reveals possible pension shortfalls. In cooperation with a major German pension fund, we conduct a field experiment, in which we vary the inflation information provided to the fund members, to explore this important issue. Among all participants, we find mostly positive but insignificant effects of the inflation information on pension contributions. Among those participants who voluntarily changed their pension contributions after the experimental intervention, the provision of inflation information significantly raises the likelihood of increasing pension contributions.
Keywords: 330; field experiment; household savings; inflation; money illusion; pension contributions